A novel safe approach to laparoscopic colorectal cancer resection in patients with ventriculoperitoneal shunt: report of two cases and literature review. Issue 1 (23rd January 2018) - Fuad, Shalabi; Doron, Kopelman; Dror, Karni; Hatoum, Ossama A
Abstract: There is ongoing challenges regarding the safety of performing laparoscopic surgery with the presence of ventriculoperitoneal (VP) shunts, especially in patients treated for cancer disease. To date, only one case has been reported in the English literature. Herein, we report an additional two cases of patients with previous insertion of a VP shunt, diagnosed with colon cancer. Both our patients underwent successful laparoscopic colectomies, without clamping or removal of the VP shunt, with no reported perioperative complications or postoperative neurological deficits. Laparoscopic bowel resection for cancer, in patients with a pre-existing VP shunt, could be considered a potentially safe and feasible procedure. Furthermore, due to the increasing number of patients with VP shunts, additional case reports and investigations are warranted to further confirm safety of this procedure.